Vorinostat Enhances Cytotoxicity of SN-38 and Temozolomide in Ewing Sarcoma Cells and Activates STAT3/AKT/MAPK Pathways - Sampson, Valerie B. (PLoS One, 2015)
Histone deacetylase inhibitors (HDACi) have been evaluated in patients with Ewing sarcoma (EWS) but demonstrated limited activity. To better understand the potential for HDACi in EWS, we evaluated the combination of the HDACi vorinostat, with DNA damaging agents SN-38 (the active metabolite of irinotecan and topoisomerase 1 inhibitor) plus the alkylating agent temozolomide (ST). Drugs were evaluated in sequential and simultaneous combinations in two EWS cell lines. Results demonstrate that cell viability, DNA damage and reactive oxygen species (ROS) production are dependent on the sequence of drug administration. Enhanced cytotoxicity is exhibited in vitro in EWS cell lines treated with ST administered before vorinostat, which was modestly higher than concomitant treatment and superior to vorinostat administered before ST. Drug combinations downregulate cyclin D1 to induce G0/G1 arrest and promote apoptosis by cleavage of caspase-3 and PARP. When ST is administered before or concomitantly with vorinostat there is activation of STAT3, MAPK and the p53 pathway. In contrast, when vorinostat is administered before ST, there is DNA repair, increased AKT phosphorylation and reduced H2B acetylation. Inhibition of AKT using the small molecule inhibitor MK-2206 did not restore H2B acetylation. Combining ST with the dual ALK and IGF-1R inhibitor, AZD3463 simultaneously inhibited STAT3 and AKT to enhance the cytotoxic effects of ST and further reduce cell growth suggesting that STAT3 and AKT activation were in part mediated by ALK and IGF-1R signaling. In summary, potent antiproliferative and proapoptotic activity were demonstrated for ST induced DNA damage before or simultaneous with HDAC inhibition and cell death was mediated through the p53 pathway. These observations may aid in designing new protocols for treating pediatric patients with high-risk EWS.